GRAMATYCZNA KATEGORIA LICZBY DLA SŁÓW OBCEGO POCHODZENIA W UJĘCIU KONFRONTATYWNYM POLSKO-ROSYJSKIM - Kwiatkowska, Tatiana (Acta Neophilologica, 2015)
This paper attempts to demonstrate symmetry and asymmetry in the adoption of foreign origin units in the linguistic systems of Polish and Russian. The in-depth analysis is dedicated to the category of number. Beginning with characteristic ending exponents of the number of nouns in both languages, certain similarities as well as differences in the ordering of borrowings into appropriate categories are indicated. The analysis concerns two aspects with respect to the research on the category of number: the first one is the adaptation of foreign nouns to a new system and the second one is the comparison of such an adaptation in Russian and Polish. The presented research findings demonstrate a diversity of factors influencing equivalence and its absence with regards to this grammatical category.